Differences between β-Ala and Gly-Gly in the design of amino acids-based hydrogels - Pasc, Andreea; Obounou Akong, Firmin; Cosgun, Sedat; Gérardin, Christine (Beilstein Journal of Organic Chemistry, 2010)
Despite the continuous interest in organogels and hydrogels of low molecular weight gelators (LMWG), establishing the relationship between the molecular structure and the gelation mechanism is still a challenge. In this paper our interest focuses on the consequences of slight molecular modifications on the self-assembling behaviour of β-Ala vs Gly-Gly-based hydrogelators. Previously, in our group, amino acid based amphiphiles i.e. Gly-Gly-His-EO2-Alk, a trimodular amphiphile (containing three domains: H-bond donor and acceptor/hydrophilic/hydrophobic domain, respectively) were reported to act as hydrogelators and that the gelation properties were related to hydrogen bonding, hydrophobic interactions and π-π stacking. Herein, β-Ala-His-EO2-Alk was fully characterised by FT-IR, NMR, SAXS and SEM and the gelation mechanism is discussed. It appears that the number of amide groups determines the self-assembling behaviour into 1D or 2D/3D networks as a result of intimate interactions between gelator molecules.
Keywords: amino acid; histidine; hydrogel; peptide-based surfactant; soft matter; supramolecular